ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP TINGKAT PENJUALAN - Hendy Eka Sumarga; Mulia Alim (Universitas Muhammadiyah Tangerang, 2016)
One early indicator to determine the condition of the progress of product marketing is through observation of the amount of product marketing results that have been done of the company. In institutions engaged in companies that produce refined products and the manufacturer is known from a list of sales results in the marketing department. This indicator is not always right but as an initial indication, can be used as indicators to examine further by way of scientific research. The purpose of this study was to determine the effect simultaneously and partially of the marketing mix that includes variable Products (X1), Price (X2), Place (X3), and Promotion (X4) on the level of sales at Rumah Makan Ayam Gantung Bandung (Y), and to determine the marketing mix most dominant influence. Methodology The study was conducted by descriptive method, which aims to explain (explanatory), the influence of variables independent of the independent variable.